Knee stability assessment on anterior cruciate ligament injury: Clinical and biomechanical approaches - Lam Mak-Ham; Fong Daniel TP; Yung Patrick SH; Ho Eric PY; Chan Wood-Yee; Chan Kai-Ming (BMC, 2009)
Abstract Anterior cruciate ligament (ACL) injury is common in knee joint accounting for 40% of sports injury. ACL injury leads to knee instability, therefore, understanding knee stability assessments would be useful for diagnosis of ACL injury, comparison between operation treatments and establishing return-to-sport standard. This article firstly introduces a management model for ACL injury and the contribution of knee stability assessment to the corresponding stages of the model. Secondly, standard clinical examination, intra-operative stability measurement and motion analysis for functional assessment are reviewed. Orthopaedic surgeons and scientists with related background are encouraged to understand knee biomechanics and stability assessment for ACL injury patients.